2019
DOI: 10.1111/jfbc.13026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nutritional composition ofMyrothamnus flabellifolius(Welw.) herbal tea and its protective effect against oxidative hepatic cell injury

Abstract: The nutrient composition of Myrothamnus flabellifolius leaf tea extract (MLTE) and its protective effect against oxidative hepatic cell injury were evaluated. Gallic acid, caffeic acid, ferulic acid, methyl gallate, and epicatechin were identified in MLTE by high‐performance liquid chromatography (HPLC). The tea extract showed an appreciable nutritional content of proximate, sugar, vitamin E, monounsaturated fatty acids, omega 6 and 9 unsaturated fatty acids, as well as considerable amounts of various mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Physiological antioxidants, including vitamin E, vitamin C and reduced glutathione are known to suppress this process, by quenching the action of prooxidants and scavenging free radical. On the contrary, plants are endowed with polyphenols, which are good antioxidant due to their electron‐donating ability (Chukwuma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Physiological antioxidants, including vitamin E, vitamin C and reduced glutathione are known to suppress this process, by quenching the action of prooxidants and scavenging free radical. On the contrary, plants are endowed with polyphenols, which are good antioxidant due to their electron‐donating ability (Chukwuma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of these sugars varied according to moisture content in plants, with fully hydrated plants containing more sugars than desiccated plants. The same researchers [ 16 ] found raffinose and stachyose at 2.49 and 2.18 g/100 g, respectively, in M. flabellifolius tea extract. In addition to α-α-trehalose (3.3% w / w ), [ 17 ] also identified raffinose (0.2% w / w ) and stachyose (0.2% w / w ), sucrose, saccharose, fructose, and fructane.…”
Section: Nutritional Composition Of Myrothamnus Flabellifol...mentioning
confidence: 89%
“…Nutritional components found in leaf extracts of M. flabellifolius include substantial amounts of dry matter, protein, fat, carbohydrates, dietary fibers, minerals and vitamins, fatty acids, reducing sugars, and cholesterol (3 mg/100 g) [ 16 ]. The same authors identified 18 essential and nonessential amino acids together with a high concentration of unsaturated fatty acids, including three, six, and nine fatty acids, suggesting potential nutritional benefits to monogastric animals.…”
Section: Nutritional Composition Of Myrothamnus Flabellifol...mentioning
confidence: 99%
“…The assay was performed according to our previously reported methods (Chukwuma et al., 2019) with very slight modifications. Chang liver cells (ATCC® CCL‐13™, American Type Culture Collection, Virginia, USA) at about 85% confluence (cultured in EMEM medium containing 10% FBS) were aliquoted (500 µl) into a 48‐well plate using fresh medium at a density of 10 000 cells/ml.…”
Section: Methodsmentioning
confidence: 99%